Nitrogen (15N) use efficiency for fertilization managements of maize and common bean using mixtures of polymer-sulfur coated urea and conventional urea - Garcia, Pedro Lopes (2021)
Nitrogen (N) is the most demanded nutrient by maize (Zea mays L.) and common bean (Phaseolus vulgaris L.) being necessary in small quantities at the beginning and at appropriate times and quantities during the growth cycle of these crops. It is desired that blends of polymer-sulfur coated urea (PSCU) and urea (U) treated with NBPT (N- (n-butyl) thiophosphoric triamide) meet the need for N of these crops with a single N application at sowing. In order to accurately recommend these blends in the current cropping systems, it is necessary to know the 15N-fertilizer recovery by plants of each N source in the blend, as well as the N dynamics in the soil - plant - atmosphere system. Thus, the objective of this study was to evaluate the 15N recovery from PSCU and/or U by plants, the ammonia volatilization from N-fertilizers applied on the soil surface, the macronutrient (N, P, K, Ca, Mg and S) uptake by plants, as well as the soil mineral N content, and grain yield. The 15N-fertilizer recovery and ammonia volatilization were evaluated in one growing season and the other analyses in two growing seasons for each crop. The experiments were conducted in a Rhodic Eutrustox soil (clayey texture), with straw on the soil surface, during the 2017-2018 and 2019-2020 maize growing seasons, and the common bean during the 2018 and 2019 irrigated growing seasons. Two blends (70% PSCU + 30% U and 30% PSCU + 70% U) were applied in three ways (incorporated application at sowing; broadcast application at sowing; and split application). The N rate was 180 kg ha-1 (maize) and 90 kg ha-1 (common bean). Control treatment (without N-fertilizer) was included. In 2019-2020, PSCU was the main N-fertilizer supplier in maize at V4 (fourth-leaf) applying 70% PSCU + 30% U, and both blends provided 73.8% of N recovery at the physiological maturity (47.9% in the grain). There was not difference in yield (12.1 Mg ha-1) and macronutrient (N, K, S, Ca and Mg) uptake among treatments in 2019-2020. In 2017-2018, 70% PSCU + 30% U provided higher yield (8.3 Mg ha-1), and the broadcast application provided higher total N and K uptake than split application and control. In the common bean, more than 50% of N from U was recovered from the blends, and the broadcast application provided lower N recovery in the grain than split and incorporated applications in 2019. In addition, the broadcast application provided lower yield (3.3 Mg ha-1) than split application and control (3.6 Mg ha-1) in the average of years. There was no difference in macronutrient uptake by common bean in both years (except N). The unrecovered N by maize and common bean can be attributed to the ammonia volatilization (~12% of the applied N), and the likely N percolation below the root zone. Based on the results, it is possible to recommend the most cost-effective treatment for maize, and opt for split or incorporated application in the common bean with the less expensive blend in the soil of the experiments